FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MASYARAKAT TERHADAP KEPATUHAN PENGGUNAAN APD (ALAT PELINDUNG DIRI) PADA MASA PANDEMI COVID-19 DI DESA SUKA MAJU - Tati Murni Karokaro; Ade Muliani; Rahmad Gurusinga; Kardina Hayati; Mila Gustia (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
December 2019 saw the discovery of a new virus in Wuhan, China, namely Corona Virus Diseases (COVID-19). This is the latest epidemic to hit the world. Covid-19 belongs to the same coronavirus family as the cause of SARS and MERS, but the death rate for SARS and MERS is higher than Covid-19 and Covid-19 has a wider and faster spread. The way to protect yourself from exposure to Covid-19 is to reduce risks such as washing your hands in running water; looking for information related to COVID-19 from valid sources, knowing what to do if you are sick. PSBB is regulated by the Regulation of the Minister of Health (RI No. 9 of 2020 concerning Guidelines for Large-Scale Social Restrictions in the context of accelerating the handling of Corona Virus Disease 2019 (Covid-19) to prevent the possible spread of the virus. Good behavior can be an effort to prevent the transmission of Covid-19 Health behavior is influenced by many factors, including knowledge, perceptions, emotions, motivation, and the environment. The purpose of this study is determine the factors that influence community behavior towards the use of personal protective equipment during the Covid-19 period in Suka Maju Village, Kec. Singingi Downstream, Kab. Kuantan Singingi, Prov. Riau. This study is an analytic observation, using a cross sectional, with a sample of 100 respondents using inclusion criteria, using a closed questionnaire. Based on this study, it was found that respondents who were obedient to the use of PPE were influenced by their good response to predisposing factors 74 respondents (93.7%). In enabling factor, respondents were obedient 22 respondents (95.7%). On the reinforcing factor, respondents who obeyed 28 respondents (93.3%).